Analisis Proses Pengendalian Manajemen Pada Dinas Pertanian Aceh Tamiang - Muhammad Zilal Hamzah; Asma'i , (Media Riset Akuntansi, Auditing & Informasi, 2006)
The aim of this research is to know does the application management of controlling process at Aceh Tamiang Agriculture Department has run better? and to identify the weakness of management controlling process at Aceh Tamiang Agriculture Department. Data is collected by interview and d Nation in part of finance conducted byAnalysis writercan be pulled by the following conclusion:Srategic plan have been put across because there are long-range planning and goals which must reach. In the case of compilation of budget there cooperation among under, middle and upper level, however financial statements often lose time because there is no punishment to the maker of overdue report. Observations of operational not yet run better because there is no part of super-visor which is independent. Its Minim of compensation to officer, make officer demotivates to work better. Given compensation is only just the main compensation.keyword; Management Process.